COVID-19 vaccination induces distinct T-cell responses in pediatric solid organ transplant recipients and immunocompetent children - Katerina Roznik; Jiashu Xue; Georgia Stavrakis; T. Scott Johnston; Divya Kalluri; Rivka Ohsie; Caroline X. Qin; John McAteer; Dorry L. Segev; Douglas Mogul; William A. Werbel; Andrew H. Karaba; et al. (npj Vaccines, 2024)
Abstract Immune responses to COVID-19 vaccination are attenuated in adult solid organ transplant recipients (SOTRs) and additional vaccine doses are recommended for this population. However, whether COVID-19 mRNA vaccine responses are limited in pediatric SOTRs (pSOTRs) compared to immunocompetent children is unknown. Due to SARS-CoV-2 evolution and mutations that evade neutralizing antibodies, T cells may provide important defense in SOTRs who mount poor humoral responses. Therefore, we assessed anti-SARS-CoV-2 IgG titers, surrogate neutralization, and spike (S)-specific T-cell responses to COVID-19 mRNA vaccines in pSOTRs and their healthy siblings (pHCs) before and after the bivalent vaccine dose. Despite immunosuppression, pSOTRs demonstrated humoral responses to both ancestral strain and Omicron subvariants following the primary ancestral strain monovalent mRNA COVID-19 series and multiple booster doses. These responses were not significantly different from those observed in pHCs and significantly higher six months after vaccination than responses in adult SOTRs two weeks post-vaccination. However, pSOTRs mounted limited S-specific CD8+ T-cell responses and qualitatively distinct CD4+ T-cell responses, primarily producing IL-2 and TNF with less IFN-γ production compared to pHCs. Bivalent vaccination enhanced humoral responses in some pSOTRs but did not shift the CD4+ T-cell responses toward increased IFN-γ production. Our findings indicate that S-specific CD4+ T cells in pSOTRs have distinct qualities with unknown protective capacity, yet vaccination produces cross-reactive antibodies not significantly different from responses in pHCs. Given altered T-cell responses, additional vaccine doses in pSOTRs to maintain high titer cross-reactive antibodies may be important in ensuring protection against SARS-CoV-2.